Penyelesaian Wanprestasi Dalam Perjanjian Jual Beli Motor Bekas - Yolanda Sefriani; Aprilla Yunita; Viola Safitri; Helfira Citra (Jurnal Kajian Hukum dan Pendidikan Kewarganegaraan, 2024)
Resolving defaults in used motorbike sale and purchase agreements is an important aspect in the business world, especially in Indonesia which has a large used motorbike market. Default, which occurs when one party fails to fulfill the obligations agreed to in the contract, can cause losses for both the seller and the buyer. This research aims to identify various methods of resolving defaults, whether through negotiation, mediation, or formal legal channels, as well as analyzing the effectiveness of each method in overcoming problems that arise. With a better understanding of dispute resolution mechanisms, it is hoped that safer and fairer transactions can be created, as well as maintaining healthy business relationships between the parties involved in buying and selling used motorbikes